Rousseau’s General Will as a Bound for Strategic Self-Interested Voting - Bodanza, Gustavo Adrian (2022)
Condorcet’s voting method, as its extension known as the Kemeny-Young rule, is often seen as the incarnation of Rousseau’s general will. But the Kemeny-Young rule has problems when cycles in the social ranking arise. In particular, it can lead to choose a “covered” alternative, i.e. one for which there are candidates with better performances in pairwise comparisons. On the other hand, the uncovered set, the set of all the alternatives that are not covered, puts limits to insincere votes of sophisticated voters under certain conditions. Basically, voting insincerelly for a non-preferred alternative in order to favor the actually preferred candidate would lead to the choice of an uncovered alternative. We argue that Rousseau’s general will could be embodied in a different kind of rule than Kemeny-Young’s, with both epistemic credentials and whose outcomes are within the uncovered set altogether. In this work we begin to explore that possibility.